P582 Adalimumab therapeutic drug monitoring: Does time of testing matter?. (15th January 2020) - Shields, S; Seenan, J P; Dunlop, A; Galloway, P; Macdonald, J
Abstract: Background: Whilst anti-TNF drugs such as adalimumab (ADL) have revolutionised the management of inflammatory bowel disease treatment outcomes are not universally favourable with 30% primary non-response (PNR) and 46% secondary loss of response (SLOR) rates reported. 1, 2 Therapeutic drug monitoring (TDM)—the measurement of serum drug levels and anti-drug antibodies—has become popular with clinicians who use it to optimise biologic therapy through serum drug-level guided dose adjustment. Conventionally TDM is based on the interpretation of trough drug levels (DL) which are obtained by drawing a blood sample immediately prior to the next drug dose. Obtaining an ADL trough DL can be challenging as the drug is administered as a subcutaneous injection usually in the patient's own home. The aim of this project was to determine the current use of non-trough ADL TDM in clinical practice and determine whether timing of ADL TDM in relation to the next planned dose is clinically important. Methods: All ADL DLs performed in 2018 in the Scottish Biologic TDM service 3 were identified. DLs were included for patients in sustained clinical remission (SCR), on 40mg every other week dosing, and if the time from the last dose was ≤14 days. TDM performed during induction and for PNR or SLOR were excluded, as were patients on nonstandard dosing or with missing data on dose and interval. Results were analysed by quartile according to time from the last drug dose. Results: 338 DLs were included. Median DL is 8µg/ml (range <0.4–36). Median time from last dose is 12 (range 0–14) days. The first quartile ( n = 83, median 5 (range 0–7) days) had a median DL of 8.2µg/ml (<0.4–28.1). The second quartile ( n = 90, median 11 (8–12) days) had a median DL of 7.9µg/ml (<0.4–36). The third quartile ( n = 80, 13 days from last dose) had a median DL of 8µg/ml (<0.4 – 28.1). fourth quartile samples ( n = 85, 14 days from last dose – true trough DLs) had a median DL of 8 µg/ml (<0.4–34.8). No relationship was identified between observed DL and the time of DL testing (ρ= -0.3162, p = 0.23). Conclusion: It is not necessary to use trough DLs when performing ADL TDM for individuals in SCR. These data should give clinicians the confidence to use opportunistic ADL TDM testing in a clinical setting. Further work should be undertaken on non-trough testing of ADL DLs in other clinical scenarios. Disclosure: Biogen GmbH contributed funding for this research. Authors had full editorial control and approval of all content. References: Ben-Horin S and Chowers. Aliment Pharmacol Ther 2011;33:987–995. Osterman MT, Haynes K, Delzell E, et al. Clin Gastroenterol Hepatol 2014;12:811–817. https://www.nhsggc.org.uk/media/251621/scottish-biologic-tdm-service-gastroenterology-guidance-03122018.pdf